Advanced cadaver‐based educational seminar for trauma surgery using saturated salt solution‐embalmed cadavers. Issue 2 (20th January 2019) - Homma, Hiroshi; Oda, Jun; Sano, Hidefumi; Kawai, Kentaro; Koizumi, Nobusato; Uramoto, Hidetaka; Sato, Norio; Mashiko, Kazuki; Yasumatsu, Hiroshi; Ito, Masayuki; Fukuhara, Tomomi; Watanabe, Yo; et al.
Abstract : Aim: Senior surgeons in Japan who participated in "cadaver‐based educational seminar for trauma surgery (CESTS)" subsequently stated their interest in seminars for more difficult procedures. Therefore, we held a 1‐day advanced‐CESTS with saturated salt solution (SSS)‐embalmed cadavers and assessed its effectiveness for surgical skills training (SST). Methods: Data were collected from three seminars carried out from September 2015 to January 2018, including a 10‐point self‐assessment of confidence levels (SACL) questionnaire on nine advanced surgical skills, and evaluation of seminar content before, just after, and half a year after the seminar. Participants assessed the suitability of the two embalming methods (formalin solution [FAS] and SSS) for SST, just after the seminar. Statistical analysis resulted in P  < 0.0167 comparing SACL results from seminar evaluations at the three time points and P  < 0.05 comparing FAS to SSS. Results: Forty‐three participants carried out surgical procedures of the lung, liver, abdominal aorta, and pelvis and extremity. The SACL scores increased in all skills between before and just after the seminar, but were decreased by half a year after. However, SACL scores of each skill did not change significantly, except for external fixation for pelvic fracture at just after and half a year after. The SSS‐embalmed cadavers were evaluated as being more suitable than FAS‐embalmed cadavers for each procedure. Conclusions: Advanced‐CESTS using SSS‐embalmed cadavers increased the participants' self‐confidence just after the seminar, which was maintained after half a year in each skill, except external fixation for pelvic fracture. Therefore, SSS‐embalmed cadavers are useful for SST, particularly for surgical repairs. Abstract : Advanced cadaver‐based educational seminar for trauma surgery using saturated salt solution‐embalmed cadavers increased the participants' self‐confidence. Saturated salt solution‐embalmed cadavers are useful for surgical skills training, particularly for surgical repairs.